Biocontrol of postharvest Alternaria decay in table grapes from Argentina - Stocco, Antonella Fabia (2019)
Postharvest diseases cause considerable losses of fruit during transportation and storage. Synthetic fungicides are primarily used to control them; however, the recent trend is to shif toward safer and more eco-friendly alternatives for the control of postharvest decays. In Argentina, Alternaria genus was cited as a postharvest pathogen in table grapes for the first time during 2010-2012 seasons. The aim of this study was to identify by morphological and molecular techniques Alternaria spp. strains isolated from table grapes cv. Red Globe in different phenological stages of vine and postharvest storage in Mendoza region. In addition, we intended to propose an alternative postharvest management to the use of sulphur dioxide (SO2) generators (traditional method). We searched for a lower environmental impact substitute; using the yeast strain Metschnikowia pulcherrima RCM2 and chitosan coatings as possible control agents. The results showed that the pathogen was present in all the stages studied and it was determined that the 100% of the strains belonged to the species-group Alternaria alternata. On the other hand, chitosan coatings showed to be a good alternative method to SO2 generators. This is the first study, to our knowledge, about Alternaria spp. incidence during the phenological cycle and postharvest storage of table grapes cv. Red Globe; and also the first study about the evaluation of alternative strategies to the use of SO2 for the control of this disease during the prolonged cold storage.